Strategi Marketing Communication Mix: Studi Kasus Wisata Alam pada Desa Minggirsari Kabupaten Blitar - Anita Reta Kusuma Wijayanti; Hesty Puspita Sari (Direktorat Riset dan Pengabdian Kepada Masyarakat, 2023)
Following the pandemic, there has been a surge in interest in natural tourismas a means to attract travelers. Minggirsari Village, since 2019, has beenactively harnessing its natural resources to entice tourists and has emerged asa trailblazing model village in Blitar Regency, successfully preserving andleveraging its natural splendors for tourism. This study endeavors to delineateMinggirsari's marketing communication strategy in promoting its naturaldestinations, employing the Marketing Communication Mix model. Thequalitative case study methodology was employed, involving on-siteobservations, interviews with tourism managers, and activity documentationto gather and subsequently analyze data, following the Miles and Hubbermentheory's stages of data collection, processing, presentation, and conclusiondrawing. Minggirsari Village's Nature Tourism employs a diverse marketingcommunications mix encompassing personal sales, advertising, promotions,and public relations to augment tourist footfall, encapsulated by the rallyingcry